Multiscale Analysis of the Interfacial Mechanical Behavior for Composite of Carbon Nanotube and α-Alumina - Tingting Yan; Gaofeng Wei (Advances in Materials Science and Engineering)
Based on multiscale methods the mechanical behavior for the interface of carbon nanotube and α-alumina is analyzed. The stress transfer between nanotube and alumina is provided by van der Waals interaction. Using cohesive law the relationship between normal stress (shear stress) and displacement is studied, as well as the stress intensity. The stress distribution of the interface is obtained by improved COX model. The strain rate of nanotube-composite is presented when the interfacial slip occurs through the van der Waals interaction.